Opinion piece: non-traditional practical work for traditional campuses. Issue 1 (1st January 2020) - Drysdale, Timothy D.; Kelley, Simon; Scott, Anne-Marie; Dishon, Victoria; Weightman, Andrew; Lewis, Richard James; Watts, Stephen
ABSTRACT: Traditional practical work for higher education in STEM subjects is under pressure from rising student numbers and adesired increase in active learning. Investing in more buildings and staff is financially challenging, while stretching existing resources affects outcomes, health, and participation. A more pragmatic approach is to embrace a less instrumentalist view of practical work in physical spaces and instead adopt a critical post-humanist approach which mixes both humanity and technology to achieve a sum greater than the parts, not bound by the limits of either. We share the experiences of leading UK exponents of non-traditional laboratories in the four main categories of simulation, virtual laboratories, real-asynchronous, and real-synchronous activities, as well as experts in scaling digital education initiatives for university-wide adoption. We foreshadow opportunities, challenges and potential solutions to increasing the opportunity for active learning by students studying at traditional campuses, via the complementary addition of non-traditional practical work.